SURVEY OF INTEREST IN LEARNING PHYSICAL EDUCATION BETWEEN STUDENTS MAJORING IN IPA AND STUDENTS MAJORING IN IPS AT SENIOR HIGH SCHOOL 1 SIMPANG KIRI SUBULUSSALAM CITY IN THE ACADEMIC YEAR 2023/2024 - Siti Sahrah; Afrizal (CV Naskah Aceh, 2025)
The purpose of this study was to obtain information about students' interest in learning physical education, sports and health at SMA Negeri 1 Simpang Kiri Subulussalam City. In this study researchers used a non-experimental quantitative approach with the type of survey research and the research design was comparative. The variables in this study are the difference between science class and social class (independent variable) and interest in learning physical education, sports, and health (dependent variable). The population in this study were all students of the Science and Social Sciences Department of SMA Negeri 1 Simpang Kiri Subulussalam City and the sample of this study were four classes. The results of the analysis of the interest of science and social studies class students towards learning physical education, sports, and health at SMA Negeri 1 Simpang Kiri Kota Subulussalam is that there is no significant difference can be seen from the results of the tcount value of 1.249 the value is declared insignificant at the 5% accuracy level because the sig. (2-tailed) value in the calculation is 0.214> more than the alpha value (a=0.05). The interest of science classes and social studies classes in learning physical education, sports and health is included in the medium category.